Program Pemulihan Ekonomi Masyarakat Pasca Bencana Erupsi Gunung Merapi di Kabupaten Klaten Jawa Tengah - C. Herutomo; Bekti Istiyanto (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2015)
The eruption of Merapi Mountain makes economical recovery be a main priority to rebuilddisaster area. The program usually are given after disaster as emergency early step and helpto victims to can live as like before. The program should be involve active people participation.This research uses qualitiative method with purpose to collect data from informan from subjectof economical recovery program at disaster location such as regional leader, bussiness subject,and people leader who be the victim of disaster. To collecting data uses indepth interview,observation and documentation. The result of this research are Klaten regional haseconomical recovery program such as emergency early helping and after disaster helping totheir people to rebuild people life; The program is valued getting successful to rebuild victimsas before disaster with develop oyster mushroom bussiness and cow farm from that program;the participation of Klaten people to this program is revivem bring to life al local wisdom“sambatan” and make people to this program.